PRESTASI MENINGKAT, KEPERCAYAAN MASYARAKAT MENGUAT, STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN JUMLAH MURID MELALUI PENINGKATAN PRESTASI SEKOLAH - Siti Mudrikah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to describe the principal’s leadership strategies in improving school achievement and rebuilding public trust through best practices implemented at SD Negeri 2 Ngenden, Ampel District, Boyolali Regency. The research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving the principal, teachers, school committee, and the surrounding community. The results show that the principal successfully transformed the school’s image from a less favored institution into a high-achieving one through collaborative, innovative, and quality-oriented strategies. The increase in both academic and non-academic achievements had a direct impact on the rise in student enrollment and community trust. Visionary leadership, effective resource management, and cross-sector collaboration proved to be key factors in the school’s transformation and sustainable improvement.